Gender barriers faced by women chefs’ in professional kitchen - Tunca, Ayça (2023)
The aim of this study is to determine the gender barriers faced by female chefs working in the kitchen departments of five-star hotels in Antalya, the factors that prevent them from progressing in their careers, and the situations they have to struggle with. In addition, it is aimed to determine the perception of gender in hotel kitchens based on the experiences of successful and well-known female chefs in professional kitchens. In the quantative part of the study it has been determined that there is no significant difference between the difficulties encountered in the business life of the female cooks participating in the research and the situations they have to struggle with and the demographic variables. In the qualitative part of the study it has been determined that female cooks working in the kitchen unit face many difficulties, both physical and psychological, such as sexual harassment, slang and mobbing. As a result, the statements made by female chefs in the study show that gender barriers continue in professional kitchens today. While working in the kitchen department, many difficulties are encountered, both physical and psychological. Regardless of their gender, women working in professional kitchens should be treated equally and fairly in the distribution and distribution of duties within the sector.